UV-C radiation in the post-harvest quality of red pitaia - Cintra de Faria, Raquel; Morgado, Cristiane Maria Ascari; Vespucci, Igor Leonardo; de Campos, André José (Comunicata Scientiae, 2022)
The cultivation of pitaya in Brazil is growing and the increase in consumption is associated with the nutritional benefits and attractiveness of the fruit. However, information about the post-harvest behavior of the fruits, in relation to their conservation potential and technologies, is incipient. In this aspect, the objective was to evaluate the postharvest quality of red pitaya submitted to different doses of UV-C radiation. The fruits were acquired from the commercial orchard in the rural area of ​​Piracanjuba-GO. The experiment was carried out in a completely randomized design, in a 4x9 factorial scheme, with four radiation doses (0; 1.81; 3.62 and 7.24 kJ m-2) and nine days of analysis (0, 2, 4, 6, 8, 10, 12, 14 and 16 days). After radiation, the fruits were placed in low density polyethylene packages (LDPE), with 1 fruit in each, being refrigerated and stored in an incubator type B.O.D. at 8±1°C, with 60±4% RH. The following were evaluated: mass loss, post-harvest conservation, soluble solids content, pH, titratable acidity, maturation index, color (°Hue, Chroma), betacyanins and carotenoids. Data were submitted to analysis of variance (P<0.05) and, when significant, regression analysis was performed. The dose of 1.81 kJ m-2 stood out in maintaining the quality of the red pitaya fruit. Pitaya treated or not with UV-C radiation, packaged in LDPE, can be kept refrigerated for up to 21 days without deteriorating.